Naturalife Inc.: an areca vegan cheese manufacturer / Muhammad Syamin Aizat Ramli ... [et al.] - Ramli, Muhammad Syamin Aizat; Misbah, Muhammad Shukhairi; Ali, Nurin Damia Dina; Sahrol @ Baharon, Nursyafiqah (2023)
Natural Life Enterprise is a cheese manufacturing company that offers high value artisan cheese made from only fresh greens for our customers. We offer high quality product with added value that are not only delicious, but also healthy and safe, which people will be happy to pay for. Our company aim is to provide cheese that are made from high quality plant-based materials for our customers. Areca Natural Cheese products are tasty and are guaranteed a meat-free solution for our customers that like to avoid consume meat to follow vegan ways and as a good healthy alternative for those who are lactose intolerant but also a cheese lover. Our product is made from plant-based material for example cashew nuts, soy, and palm oil. In terms of health, vegan cheese is generally considered a better choice that dairy cheese as vegan cheese is lower in terms of saturated fat, rich in vitamins such as B12 and vitamin D and contains nutrients like potassium and sodium. We are always looking forward for our customers satisfaction towards our products. Our company would be supplying cheese on a business-to business basis to entities such as restaurants, bakeries, groceries and more. As a new company and a pioneer of manufacturing different type of cheese locally, there will be a great number of aspects that we will need to take count for to ensure our company can compete with other cheese brands in the market to fulfil our customer needs. Our products are different than others in the market as we offer cheese that are not made from animal products, which has almost zero cholesterol and trans -fat. Our cheese is typically lower in fat, free from additives and gluten-free which are what most people want in an ideal cheese product which help people to follow vegan ways, to lose weight and have a healthy diet. ENT300/ETR300 BP OUTLINE (as at 23 Jan 2023) Our business is run by four main executives which are Tuan Aizat, Encik Shukhairi, Puan Mia Dina and Cik Syafiqah. All of us play a vital role in our business to ensure that our business will be successful and make a name throughout Malaysia as a Bumiputera product. Based on our observations, research and statistic gathered, we are targeting a big scope of business and customers as our company is in a city with wide population which will enhance our chances of getting customers and raise the name of local product. Our business is located near many marketplaces like supermarkets and shop lots and near residential areas. We believe in our capabilities as a company to achieve our goal and meet the expectations of our customers. With our products produce with good quality control to make sure it meets the required standards for a guaranteed flawless cheese product for our customers. Our company has three types of cheese products which are Mozzarella, Parmesan and Cheddar. We hope that our Natural Life Enterprise can be a well-known and creates name for itself as a local product and will be people’s choice in the future.